Circle Problem

Geometry Level 4

In the circle above chords A C AC and B E BE intersect at D D , where B D = a BD = a , D E = a + 4 DE = a + 4 and D C = a + 2 DC = a + 2 .

If the radius of the circle r = 2 5 r = 2\sqrt{5} and a a can be expressed as a = α β + α α α λ α a = \sqrt{\alpha \beta + \alpha^{\alpha}\sqrt{\alpha \lambda}}- \alpha , where α \alpha , β \beta and λ \lambda are coprime positive integers, find α + β + λ \alpha + \beta + \lambda .


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let the center of the circle be the origin O ( 0 , 0 ) O(0,0) and the line B E BE is b b above O O . Then in coordinates, E ( a + 2 , b ) E(a+2, b) and C ( 2 , b ( a + 2 ) ) C(-2, b-(a+2)) . By Pythagorean theorem, we have:

{ O E 2 : ( a + 2 ) 2 + b 2 = r 2 O C 2 : ( 2 ) 2 + ( b ( a + 2 ) ) 2 = r 2 \begin{cases} OE^2: & (a+2)^2 + b^2 = r^2 \\ OC^2: & (-2)^2 + (b-(a+2))^2 = r^2 \end{cases}

( a + 2 ) 2 + b 2 = 4 + ( b ( a + 2 ) ) 2 = 4 + b 2 2 b ( a + 2 ) + ( a + 2 ) 2 2 b ( a + 2 ) = 4 b = 2 a + 2 \begin{aligned} \implies (a+2)^2 + b^2 & = 4 + (b-(a+2))^2 \\ & = 4 + b^2 - 2b(a+2) + (a+2)^2 \\ \implies 2b(a+2) & = 4 \\ b & = \frac 2{a+2} \end{aligned}

Putting in O E 2 OE^2 :

( a + 2 ) 2 + 4 ( a + 2 ) 2 = r 2 ( a + 2 ) 4 20 ( a + 2 ) 2 + 4 = 0 ( a + 2 ) 2 = 20 + 2 0 2 16 2 = 10 + 4 6 a = 10 + 4 6 2 In response to Peter Csorba’s comments = 2 + 6 2 = 6 \begin{aligned} (a+2)^2 + \frac 4{(a+2)^2} = r^2 \\ (a+2)^4 - 20(a+2)^2 + 4 & = 0 \\ \implies (a+2)^2 & = \frac {20+\sqrt{20^2-16}}2 = 10 + 4\sqrt 6 \\ a & = \boxed{\sqrt{10+4\sqrt 6} - 2} & \small \blue{\text{In response to Peter Csorba's comments}} \\ & = 2 + \sqrt 6 - 2 = \sqrt 6 \end{aligned}

Therefore α + β + γ = 2 + 5 + 3 = 10 \alpha + \beta + \gamma = 2+5+3 = \boxed{10} .

a = 6 a = \sqrt{6}

Peter Csorba - 1 year, 5 months ago

Log in to reply

Thanks. You should also inform @Rocco Dalto , who set the problem.

Chew-Seong Cheong - 1 year, 5 months ago

Log in to reply

I didn't realize that ( 2 + 6 ) 2 = 4 + 4 6 + 6 = 10 + 4 6 2 + 6 = 10 + 4 6 (2 + \sqrt{6})^2 = 4 + 4\sqrt{6} + 6 = 10 + 4\sqrt{6} \implies 2 + \sqrt{6} = \sqrt{10 + 4\sqrt{6}} .

Although, I stated in the problem that a a can be expressed as a = α β + α α α λ α a = \sqrt{\alpha \beta + \alpha^{\alpha}\sqrt{\alpha \lambda}}- \alpha so that the problem is still correct.

Rocco Dalto - 1 year, 5 months ago
Rocco Dalto
Jan 8, 2020

Let ( x 0 , y 0 ) (x_{0},y_{0}) be the center of the circle.

x 0 ( a + 4 ) ) 3 + y 0 2 = r 2 x_{0} - (a + 4))^3 + y_{0}^2 = r^2

( x 0 + a ) 2 + y 0 2 = r 2 (x_{0} + a)^2 + y_{0}^2 = r^2

Subtracting the two equations we obtain:

4 ( a + 2 ) x 0 = 8 ( a + 2 ) x 0 = 2 4(a + 2)x_{0} = 8(a + 2) \implies x_{0} = 2 .

For y 0 : y_{0}:

Using x 0 = 2 x_{0} = 2 we have:

( a + 2 ) 2 + y 0 2 = r 2 (a + 2)^2 + y_{0}^2 = r^2

4 + ( y 0 + ( a + 2 ) ) 2 = r 2 4 + (y_{0} + (a + 2))^2 = r^2

Subtracting the two equations we obtain:

2 ( a + 2 ) y 0 = 4 y 0 = 2 a + 2 -2(a + 2)y_{0} = 4 \implies y_{0} = \dfrac{-2}{a + 2}

\implies

( a + 2 ) 2 + 4 ( a + 2 ) 2 = 20 ( a + 2 ) 4 20 ( a + 2 ) 2 4 = 0 (a + 2)^2 + \dfrac{4}{(a + 2)^2} = 20 \implies (a + 2)^4 - 20(a + 2)^2 - 4 = 0 \implies

a = ± 10 ± 4 6 2 a = \pm\sqrt{10 \pm 4\sqrt{6}} - 2

The only positive real root is a = 10 + 4 6 2 = 2 5 + 2 2 2 3 2 = a = \sqrt{10 + 4\sqrt{6}} - 2 = \sqrt{2 * 5 + 2^2\sqrt{2 * 3}} - 2 =

α β + α α α λ α α + β + λ = 10 \sqrt{\alpha * \beta + \alpha^{\alpha}\sqrt{\alpha * \lambda}}- \alpha \implies \alpha + \beta + \lambda = \boxed{10} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...